2019
DOI: 10.1177/0885066619884896
|View full text |Cite
|
Sign up to set email alerts
|

Survival Impact and Clinical Predictors of Acute Gastrointestinal Bleeding in Patients With Bloodstream Infection

Abstract: Purpose: The impact of gastrointestinal bleeding (GIB) on outcomes of patients with bloodstream infection (BSI) has not been studied. We aim to evaluate the risk factors and survival impact of GIB on the outcome of BSI. Materials and Methods: This study was conducted prospectively at National Taiwan University Hospital Yunlin Branch between January 1, 2015, and December 31, 2016. Patients aged ≥18 years for who BSI was confirmed by blood cultures were enrolled and followed for 90 days. Risk factors of GIB were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Therefore, careful attention should be paid to the use of tigecycline in ICU patients. The gastrointestinal tract has long been considered to have an important regulatory role 15 , and BSI patients with gastrointestinal bleeding has higher in-hospital mortality 16 , 17 . The result of our research also found a significant correlation between gastrointestinal bleeding and the occurrence of BSI, supporting the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, careful attention should be paid to the use of tigecycline in ICU patients. The gastrointestinal tract has long been considered to have an important regulatory role 15 , and BSI patients with gastrointestinal bleeding has higher in-hospital mortality 16 , 17 . The result of our research also found a significant correlation between gastrointestinal bleeding and the occurrence of BSI, supporting the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Amy et al showed that gastrointestinal bleeding had a negative impact on the short-term survival of patients with BSI. 37 However, the underlying mechanism remains unclear, and more studies are needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although severe GI bleeding isn't a typical outcome of enteric infection, it is a substantial burden on human health, affecting around 40-150 out of every 100,000 individuals annually, with a fatality rate ranging from 6% to 30% (Fig. 1) 3,13,[18][19][20][20][21][22][23] . Enterobacteriaceae are prone to bloodstream entry and are a leading cause of sepsis-related deaths in individuals with inflammatory bowel diseases (IBD) that have recurrent enterohemorrhagic lesions 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, GI bleeding is associated with significant risk of mortality, in the range of 6-30%, and impacts 40-150 of every 100,000 individuals annually (Fig. 1) (Aljarad and Mobayed, 2021;Huang et al, 2021;Kim et al, 2014Kim et al, , 2014Moledina and Komba, 2017;Saltzman, 2022;Scales and Huffnagle, 2013;Tacconelli et al, 2018;Zhou et al, 2022). GI pathogens demonstrate specific affinity for inflamed and damaged tissue (Fig.…”
Section: Introductionmentioning
confidence: 99%